Assessing the status quo the level of satisfaction of people in Molo Plaza complex
The researcher evaluated the current status of Molo Plaza based on the principles of sociability, access and linkages, uses and activities, and comfort and image from Project of Public Spaces. A relevant objective was to identify and describe the issues and problems at Molo Plaza Complex. To attain the objectives, a survey was coducted with 160 respondents supplemented by participant observation, an informal interview with s staff of Molo Plaza Police Station and photographs taken at the study site. Secondary sources were also utilized to support the primary sources.The study reveals that the current status of the Molo Plaza Complex conforms to the three key attributes used to evaluate the place. However, the management of the Molo Plaza Complex has to focus its attention towards some aspects such as mix of stores or services, frequency through utilizing the survey results as the respondents were tasked to rate every dimension into "Poor'" "Fair," "Good" and "Satisfactory." Whereas, the dimensions rated as "Poor" and "Fair" in the overall results were the factors that needs more consideration as it signifies non-comformity to the standards provided by the PPS and the dimensions with "Good" and "Satisfactory" ratings were considered as the ones conforming to the standards.Respondents provided practical recommendations for the improvement of the plaza which include proper management, tight security and safety, and construction of facilities such as water fountain, comfort room and playground.